Hyaluronic Acid Improves the Tolerability of Hypertonic Saline in the Chronic Treatment of Cystic Fibrosis Patients: A Multicenter, Randomized, Controlled Clinical Trial - Ros, Mirco; Casciaro, Rosaria; Lucca, Francesca; Troiani, Patrizia; Salonini, Elena; Favilli, Federica; Quattrucci, Serena; Sher, Daniel; Assael, Baroukh Maurice (Journal of aerosol medicine, 2014)
Abstract Trial Design and Methods: Between December 2009 and July 2011, four cystic fibrosis (CF) centers in Italy participated in a randomized, double-blind, controlled clinical trial to test whether 7% hypertonic saline (HS) administered together with 0.1% hyaluronic acid (HA) was better tolerated by patients who previously did not tolerate HS well on its own. Participants were CF patients at least 8 years old, in clinically stable conditions, with forced expiratory volume in 1 sec (FEV1) at least 50% predicted. Forty patients were recruited and randomized to receive either HS or HS plus HA (5 mL to be inhaled over 15 min, twice daily for 28 days). Primary endpoints were cough, throat irritation, salty taste, and overall acceptability, as assessed by each patient on a semiquantitative scale on a diary card. Secondary endpoint was FEV1 change at the end of treatment. Patients were randomized into randomly permuted blocks. The first and last doses were administered in hospital. In between, patients were treated at home. Patients, all caregivers, and the statistician who conducted the analysis (different from the one who generated the random list) were blinded to group assignment. Results: Severity of cough, throat irritation, and saltiness were more severe in patients treated with HS alone, both after the first inhalation and over the entire treatment period. Overall pleasantness was rated higher by patients treated with the combination product. All differences were highly significant. There were no changes in FEV1 between the first and last administrations. Five patients did not complete the study. Four patients (two from each group) withdrew because of cough or throat irritation. One more patient from the HS group withdrew because of a respiratory exacerbation at week 3. Conclusions: HS is currently a cornerstone in the treatment of CF patients. The addition of HA to HS reduces the prevalence and severity of cough, throat irritation, and saltiness and may improve compliance in patients who previously did not tolerate HS well on its own. Longer-term studies could further assess the benefit of chronic treatment.